Cytotoxic mycoepoxydiene derivatives from an endophytic fungus Phomopsis sp. isolated from Hydnocarpus anthelminthicus - Surasak Prachya (2018)
Mycoepoxydiene (1) and derivatives, deacetylmycoepoxydiene (2) and 2,3-dihydromycoepoxydiene (3), were isolated from a broth extract of the endophytic fungus, Phomopsis sp., which was isolated from a Thai medicinal plant, Hydnocarpus anthelminthicus. Compounds 1 and 2 exhibited potent cytotoxic activity, while a dihydro derivative 3 was inactive. The present work suggests that the α,β-unsaturated lactone moiety in mycoepoxydienes might be responsible for the cytotoxicity. © Georg Thieme Verlag KG Stuttgart.